2014
DOI: 10.5423/rpd.2014.20.1.025
|View full text |Cite
|
Sign up to set email alerts
|

Mating Types of Phytophthora infestans Isolates and Their Responses to Metalaxyl and Dimethomorph in Korea

Abstract: Phytophthora infestans was isolated from potato leaves collected from main potato producing areas in Korea during 2009-2011. In 2009, 99 isolates tested were all A1 mating type. Two of 64 isolates in 2010 and two of 78 isolates in 2011 were A2 mating type and they were found only in Miryang area. Among 99 isolates examined in 2009, 13.1% was resistant to metalaxyl, 3.1% was intermediate resistant and 83.8% was sensitive. In 2010, 19.4% of 62 isolates was resistant, 4.8% was intermediate and 75.8% was sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…No isolates resistant to dimethomorph were detected in different years and sample locations in the present study. Similarly, Kim et al (2014) reported that there were no isolates collected in South Korea from 2009 to 2011 that could grow on 5 µg/ml dimethomorph, while Gisi and Sierotski (2015) stated that, to date, no field isolates of any Phytophthora sp.resistant to CAA (carboxylic acid amide) fungicides (the group to which dimethomorph belongs) have been discovered. The South Korean P .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…No isolates resistant to dimethomorph were detected in different years and sample locations in the present study. Similarly, Kim et al (2014) reported that there were no isolates collected in South Korea from 2009 to 2011 that could grow on 5 µg/ml dimethomorph, while Gisi and Sierotski (2015) stated that, to date, no field isolates of any Phytophthora sp.resistant to CAA (carboxylic acid amide) fungicides (the group to which dimethomorph belongs) have been discovered. The South Korean P .…”
Section: Discussionmentioning
confidence: 99%
“…infestans genetic diversity than the other production regions. In this region, potatoes are grown in plastic tunnels during the winter season when late blight is more prevalent than in other regions because of high humidity and low temperatures (Kim et al , 2014). Frequently applied chemical control measures, including the use of metalaxyl, may have generated sufficient variable selection pressure to result in slightly more genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations